A Novel Mouse Model of Subcortical Infarcts with Dementia - Hattori, Yorito (J Neurosci, 2015)
Subcortical white matter (WM) is a frequent target of ischemic injury and extensive WM lesions are important substrates of vascular cognitive impairment (VCI) in humans. However, ischemic stroke rodent models have been shown to mainly induce cerebral infarcts in the gray matter, while cerebral hypoperfusion models show only WM rarefaction without infarcts. The lack of animal models consistently replicating WM infarct damage may partially explain why many neuroprotective drugs for ischemic stroke or VCI have failed clinically, despite earlier success in preclinical experiments. Here, we report a novel animal model of WM infarct damage with cognitive impairment can be generated by surgical implantation of different devices to the right and left common carotid artery (CCA) in C57BL/6J mice. Implantation of an ameroid constrictor to the right CCA resulted in gradual occlusion of the vessel over 28 d, whereas placement of a microcoil to the left CCA induced ∼50% arterial stenosis. Arterial spin labeling showed a gradual reduction of cerebral blood flow over 28 d post operation. Such reductions were more marked in the right, compared with the left, hemisphere and in subcortical, rather than the cortical, areas. Histopathological analysis showed multiple infarct damage in right subcortical regions, including the corpus callosum, internal capsule, hippocampal fimbria, and caudoputamen, in 81% of mice. Mice displaying such damage performed significantly poorer in locomotor and cognitive tests. The current mouse model replicates the phenotypes of human subcortical VCI, including multiple WM infarcts with motor and cognitive impairment.